2007
DOI: 10.1007/s00277-006-0211-4
|View full text |Cite
|
Sign up to set email alerts
|

Pure red-cell aplasia secondary to pregnancy, characterization of a syndrome

Abstract: The aim of this study was to characterize the syndrome of pure red-cell aplasia (PRCA) secondary to pregnancy. All published cases of PRCA induced by pregnancy were reviewed. Additionally, we reported a patient who developed PRCA on three occasions; two were triggered by pregnancy and one after medroxyprogesterone administration. Ten patients with 13 pregnancy-induced PRCA episodes were reported. The PRCA occurred at any gestational age. All patients received blood transfusions, and six of them were treated co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
13

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 8 publications
0
7
0
13
Order By: Relevance
“…7,22 In humans, pregnancy has also been associated with immune-mediated PRCA. 23 Acquired autoimmune-mediated mechanisms are thought to be the main process for PRCA in cats, dogs, and humans because antibodies destroy erythroid precursors in the bone marrow. 7,8 Antinuclear antibody titers were evaluated in this ferret, and results were negative; it was the only screening test available (in addition to the slide agglutination test) that could be used to assess autoimmune hemolytic diseases in ferrets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,22 In humans, pregnancy has also been associated with immune-mediated PRCA. 23 Acquired autoimmune-mediated mechanisms are thought to be the main process for PRCA in cats, dogs, and humans because antibodies destroy erythroid precursors in the bone marrow. 7,8 Antinuclear antibody titers were evaluated in this ferret, and results were negative; it was the only screening test available (in addition to the slide agglutination test) that could be used to assess autoimmune hemolytic diseases in ferrets.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, 1 form of immune-mediated PRCA in humans is associated with pregnancy. 23 The pathogenesis of PRCA during pregnancy in humans is largely unknown. It has been suggested that hormonal disturbances can cause anemia through direct effects on red cell precursors or by induction of autoimmunity.…”
Section: Discussionmentioning
confidence: 99%
“…PRCA in pregnancy has a better prognosis compared to pre-existing PRCA and aplastic anemia in pregnancy. In general, PRCA that develops during pregnancy spontaneously resolves postpartum [ 8 ]. Although it rarely recurs in subsequent pregnancy, recurrence was observed here and hence the permanence of PRCA is not known [ 3 ].…”
Section: To the Editormentioning
confidence: 99%
“…Se hace síntesis narrativa de los hallazgos. diez estudios relacionados con anemia aplásica eritroide pura asociada a embarazo: seis reportes de casos (4,7-11,) tres reportes de caso con revisión de la literatura (6,12,13), un reporte de caso en la modalidad de poster (5), para un total de 10 casos reportados (tabla 1).…”
Section: Materiales Y Métodosunclassified
“…Se ha propuesto que las progestinas juegan un papel en la génesis, de tal forma que los cambios hormonales durante el embarazo desencadenan un mecanismo autoinmune en pacientes predispuestas que lleva a inhibición de colonias eritroides, lo que sugiere una respuesta autoinmune humoral (4-5), y la presencia en la sangre periférica de la madre y células placentarias de un factor inhibidor que afecta la eritropoyesis y diferenciación eritroide (6). El diagnóstico de la AEP en el embrazo es por descarte y los hallazgos de la biopsia de médula ósea y la recuperación de los niveles de hemoglobina en pocas semanas posteriores al parto soporta aún más el diagnóstico (6). El tratamiento estaría basado en múltiples transfusiones de hemoderivados durante su periodo gestacional para mantener los niveles de hemoglobina, con riesgo de reacciones secundarias.…”
Section: Introductionunclassified